Prevalence and associated risk factors for depression symptoms in adolescent girls with polycystic ovary syndrome: a hospital-based cross-sectional study - Wang, Lianhong; Su, Sihui; Xiong, Tingting; Wang, Meili; Ding, Rui; Tan, Huiwen; Zhu, Minglan (Frontiers in Public Health, 2024)
Background Depression symptoms are a growing concern for adolescent girls with PCOS around the world. However, relatively small samples have given varying reports of its prevalence and risk factors in previous studies. Therefore, there is an urgent need for further research on the prevalence and associated factors of depression among adolescent girls with PCOS. Methods A cross-sectional study was performed from October 2021 to May 2022 using a questionnaire and examination of the medical records of a convenience sample of 335 adolescent girls with PCOS. The Chinese version of the Children’s Depression Scale (CDI) was used to investigate depression symptoms. A multivariate logistic regression model was used to determine factors that were significantly associated with depression symptoms. Results The prevalence of depression symptoms was 36.12% among adolescent girls with PCOS. A multivariate logistic regression model identified significant factors as perceived social support (95% CI: 0.921 ~ 0.965%, p = 0.000), sleep quality (95% CI: 1.134 ~ 1.324%, p = 0.000), belief illness (95% CI, 1.040 ~ 1.102%, p = 0.000), hirsutism (95% CI, 1.292 ~ 4.392%, p = 0.005), and LH/FSH ≥ 2 (95% CI, 1.939 ~ 6.369%, p = 0.000). Conclusion Depression symptoms are an important problem among adolescent girls with PCOS in China. A comprehensive approach that encompasses social support, structured health education for the disease, and evaluation of the psychological status of PCOS girls with hirsutism (and) or LH/FSH ≥ 2 in time is important to minimize depression symptoms and improve psychological health among adolescent girls with PCOS.